Language Birth - Mac Aditiawarman (Jurnal Ilmiah Langue and Parole, 2017)
Language birth is a kind of event where a language appear and used by the community. Language birth through long process. Language birth can be formed by mixing of two or more languages. The formation of a new language is usually the result of a mixture of vocabulary. The mixing of the vocabulary will be mastered by one of the languages called the matrix language. The matrix language has a strong position in the new language because the matrix language controls the development of the new language. Merging two or more languages takes considerable time until the language becomes a new permanent language like Tiong Pa language in Padang, West Sumatera, Indonesia.